Mekanisme Pemakzulan Presiden dan/atau Wakil Presiden Menurut UUd 1945 (Antara Realitas Politik dan Penegakan Konstitusi) - Muhammad Bahrul Ulum (Jurnal Konstitusi, 2016)
The Inquiry rights was the implementation of the oversight function of House Representative (DPR) to Presiden/and  or Vice President. The  use  of  inquiry  right  as  a  political  strategy  in impeachment mechanism to President/and or Vice President depend on reality and political consensus of the DPR, so there are possibilities and tendencies that the rule of law and democracy    are not be able to maintained as stipulated in Article 1 the 1945 Constitution. The decree of impeachment of the President and/or Vice President as provide in the 1945 Constitution tend unable  to uphold the rule of law when the Constitutional Court decided the President and / or Vice President violated the constitution, namely the dismissal of the President and or the Vice President made by the Assembly through a political decision (politeke beslssing). The efforts to maintains consistency of the concept of law as stipulated in Article 1 paragraph (3), Article 7B paragraph (3) and paragraph (7) of the 1945 Constitution, without opening  the chance intervention of political interests and obligations of the Assembly to implement the decision of the Constitutional Court. Therefore, the rule of law must be a cornerstone in the practice of constitutional law in  Indonesia.